On the Black Diaspora: Lessons from the French Context - (:unkn) unknown (My University, 2006)
In the last fifteen years, the reflection on the African Diaspora has been granted a very significant place in the Anglo-American academia. In contrast, in France, the social sciences have appeared uninterested in this literature. Yet, French researchers have many reasons to take part in this reflection. Since the interwar period, France has been a major site for activists working towards the construction of a Black diasporic identity. Because of segregationist laws in the US, the American occupation of Haiti, and the lack of (post-) secondary education in its African colonies, France has been the destination of thousands of young Blacks among whom a significant proportion of intellectuals, writers and students. Moving beyond its ethnic, national and linguistic differences among its members, these elite took on the ambitious objective of coordinating Blacks all around the world for the emancipation of Africa and the black race. This article questions the epistemological foundations of the dearth of reflection on Black diaspora in the French social sciences.
Keywords: African Research